2021
DOI: 10.1186/s12882-021-02339-5
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemic waist phenotype and risk of chronic kidney disease in community-dwelling adults aged 60 years and older in Tianjin, China: a 7-year cohort study

Abstract: Background The hypertriglyceridemic waist (HTGW) phenotype has been proposed to be related to the occurrence and progression of chronic kidney disease (CKD). The ageing trend of the Chinese population continues to intensify, and elderly individuals are at high risk of CKD. The purpose of this study was to investigate the cross-sectional and longitudinal associations between the HTGW phenotype and the risk of CKD by following community-dwelling adults aged 60 years and older in Tianjin, China, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Our assessment of study quality using the NOS tool showed that both included cohort studies had good quality, with one study 23 having a total score of 8 and the other study 24 having a total score of 9. In addition, all the included cross-sectional studies were good quality, with total scores of 8 or 9 on the modified NOS tool.…”
Section: Resultsmentioning
confidence: 93%
“…Our assessment of study quality using the NOS tool showed that both included cohort studies had good quality, with one study 23 having a total score of 8 and the other study 24 having a total score of 9. In addition, all the included cross-sectional studies were good quality, with total scores of 8 or 9 on the modified NOS tool.…”
Section: Resultsmentioning
confidence: 93%
“…Triglycerides were measured using an enzymatic color metric test, with an elevated triglyceride level defined as ≥ 1.5 mmol/L for females or ≥ 2.0 mmol/L for males. Waist circumference was measured by trained assessors using soft measuring tape, and enlarged waist circumference was defined as ≥ 85 cm in females or ≥ 90 cm in males [9,10]. We divided participants into the following four triglyceride-waist phenotypes: 1) NTNW, normal triglyceride levels and normal waist circumference; 2) NTGW, normal triglyceride levels and enlarged waist circumference; 3) HTNW, elevated triglyceride levels and normal waist circumference; and 4) HTGW, elevated triglyceride levels and enlarged waist circumference [10].…”
Section: Exposure and Outcomementioning
confidence: 99%
“…Previous studies reported that elevated triglycerides and enlarged waist circumference were associated with a higher risk of hyperuricemia [7,8]. The hypertriglyceridemic-waist (HTGW) phenotype (i.e., coexistence of elevated triglyceride levels and enlarged waist circumference) was first introduced in 2000 and has been confirmed as a measure of increased visceral adiposity and a predictor of chronic kidney disease [9,10]. A previous study determined the potential mechanism among them, i.e., insulin resistance induced by visceral obesity subsequently reduces the excretion of uric acid from the renal system, resulting in an increased risk of hyperuricemia [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is also significantly correlated with early diabetic nephropathy in type 2 patients with diabetes 17. In a community-based cohort study conducted in China, it was independently associated with an increased risk of chronic kidney disease (CKD) prevalence and development in the elderly, aged ≥60 years 18. The HTGW phenotype is determined by measuring two components: the waist circumference (WC) and blood triglyceride levels.…”
Section: Introductionmentioning
confidence: 99%
“… 17 In a community-based cohort study conducted in China, it was independently associated with an increased risk of chronic kidney disease (CKD) prevalence and development in the elderly, aged ≥60 years. 18 The HTGW phenotype is determined by measuring two components: the waist circumference (WC) and blood triglyceride levels. Also, it is anticipated to be a predictive marker for the risk of AP.…”
Section: Introductionmentioning
confidence: 99%